Genetic and epigenetic effects on couple adjustment in context of romantic relationship: A scoping systematic review - Khani, Pouria; Ansari Dezfouli, Mitra; Nasri, Farzad; Rahemi, Maryam; Ahmadloo, Salma; Afkhami, Hamed; Saeidi, Farzane; Tereshchenko, Sergey; Bigdeli, Mohammad Reza; Modarressi, Mohammad Hossein (Frontiers in Genetics, 2023)
Couples relationships are defined by a complex interaction between the two partners and their individual intra-personal traits. Romantic relationship and love is associated with marital satisfaction and stability, as well as couples’ happiness and health. Personality traits Influence on romantic relationships and personality is influenced by genetic and environmental factors. The roles of non-genetic factors such as socioeconomic position, external appearance and personality characteristics are revealed in determining the quality of romantic relationships. We performed a scoping systematic review to assess the association between the genetics and epigenetic factors and romantic relationship. Relevant articles Identified by PubMed, EMBASE, Web of Science, Scopus and the APA PsycInfo searching between inception and 4 June 2022. Different studies evaluated the associated polymorphisms in 17 different genes or chromosomal regions. At the first step we classified them into four groups: (1) Oxytocin- related signaling pathway (OXTR, CD38, and AVPR1A); (2) Serotonin-related signaling pathway (SLC6A4, HTR1A and HTR2A); (3) Dopamine and catecholamine-related signaling pathway (DRD1, DRD2, DRD4, ANKK1, SLC6A3 and COMT); and (4) other genes (HLA, GABRA2, OPRM1, AR and Y-DNA haplogroup D-M55). Then, we evaluated and extracted important polymorphisms that influence couple adjustment and romantic relationship. Overall, the findings suggest that genetic and epigenetics variants play a key role in marital adjustment and romantic relationship over time.